Chemo-Profiling of Illicit Amphetamine Tablets Seized from Jazan, Saudi Arabia, Using Gas Chromatography-Mass Spectrometry and Chemometric Techniques - Hassan A. Alhazmi; Waquar Ahsan; Mohammed Al Bratty; Asaad Khalid; Shahnaz Sultana; Asim Najmi; Hafiz A. Makeen; Ibraheem M. Attafi; Farid M. Abualsail; Mohammed A. Arishy; Ibrahim A. Khardali (Journal of Chemistry)
A number of illegal drug tablets with unknown constituents are supplied to countries around the world, most of which are habit forming. Amphetamine constitutes the majority of illegal tablets supplied to Saudi Arabia. In this study, we investigated illicit amphetamine tablets seized from Jazan region located in the southwest of Saudi Arabia to identify the insidious additives present in them and their health-related risks. Tablets were analyzed for the presence of amphetamine and other additives using gas chromatography-mass spectroscopy (GC-MS) technique. Amphetamine was detected in good to high area % values in all analyzed tablets in the range of 16.29–41.23%. Interestingly, a number of other additives were also detected with amphetamine in most of the tested samples including caffeine, lidocaine, diphenhydramine, and 8-chlorotheophylline in considerable area %. Caffeine may have been added to enhance the psychotic effect of amphetamine, whereas lidocaine was added to prevent the cardiovascular side effects of amphetamine. Diphenhydramine was probably added to prevent other undesirable side effects of amphetamine such as insomnia and tremors. Chemometric hierarchical cluster analysis was carried out to make samples clusters which have similar characteristics. It resulted into a dendrogram tree showing eight clusters signifying different sources of tablet samples. Owing to the toxic effects of amphetamine and other psychoactive constituents in the tested tablets, the illegal trafficking of these tablets should be prevented by all means and public awareness should be increased.